Influenza in the tropics - Moura, Fernanda E A (Current opinion in infectious diseases, 2010)
Data on influenza in tropical countries remain scarce compared with that in temperate countries. However, the emergence of avian influenza virus (H5N1) and the 2009 pandemic represented a major stimulus for advances in knowledge about influenza in many of these countries. This review summarizes recent data on viral and epidemiologic aspects of the condition in tropical countries. Avian influenza and the influenza pandemic of 2009 have contributed to pioneer production of data on influenza in the tropical settings. Preliminary data on epidemiology, genetic diversity, and antiviral resistance of influenza viruses (seasonal and pandemic) in tropical countries have been published recently. The seasonality of influenza is very diverse in tropical countries. Recent studies on the subject confirm the year-round activity of these viruses in many countries and the regular occurrence of epidemic outbreaks in others. The use of molecular diagnostic methods has led to prevalence rates comparable to those seen in temperate countries. Phylogenetic analysis of hemagglutinin of influenza isolates allows understanding of the evolution and divergence of avian (H5N1) and human influenza viruses (A/H1N1, A/H3N2, and B) in tropical settings. Influenza viruses resistant to oseltamivir and zanamivir have been detected in tropical countries despite the rare use of these drugs in the treatment of influenza in people living in these areas.